Novel synthetic curcumin analogs as potent antiangiogenic agents in colorectal cancer. Issue 1 (29th April 2016) - Rajitha, Balney; Nagaraju, Ganji Purnachandra; Shaib, Walid L.; Alese, Olatunji B.; Snyder, James P.; Shoji, Mamoru; Pattnaik, Subasini; Alam, Afroz; El‐Rayes, Bassel F.
Abstract : The transcription factor NF‐κB plays a central role in angiogenesis in colorectal cancer (CRC). Curcumin is a natural dietary product that inhibits NF‐κB. The objective of this study is to evaluate the antiangiogenic effects of curcumin and two potent synthetic analogues (EF31 and UBS109) in CRC. IC50 values for curcumin, EF31, and UBS109 were determined in the HCT116 and HT‐29 cell lines. HUVEC tube formation, egg CAM assay, and matrigel plug assays revealed decreased angiogenesis in cell lines treated with curcumin, EF31, or UBS109. Curcumin and its analogues significantly inhibited VEGF‐A synthesis and secretion in both cell lines in association with loss of HIF‐1α, COX‐2, and p‐STAT‐3 expression. Nuclear NF‐κB expression was inhibited by curcumin, EF31, and UBS109. Transfection of p65‐NF‐κB in HCT116 and HT‐29 cells resulted in increased expression of HIF‐1α, COX‐2, STAT‐3, and VEGF‐A. Treatment with curcumin, EF31, or UBS109 inhibited these effects in transfected cell lines. In mice carrying HCT116 and HT‐29 cell xenografts, EF31 and UBS109 inhibited subcutaneous tumor growth and potentiated the effects of oxaliplatin and 5‐FU. Tumors from treated animals revealed inhibition of HIF‐1α, COX‐2, p‐STAT‐3, and VEGF expression. Our findings suggest that inhibition of NF‐κB leading to decreased transcription and expression of HIF‐1α, COX‐2, STAT‐3, and VEGF is a rational approach for antiangiogenic therapy in CRC. The distinctive properties of EF31 and UBS109 make them promising therapeutic agents for development in CRC as single agents or as part of combination chemotherapy regimens. © 2016 Wiley Periodicals, Inc.